Oxotitanium(IV) Complexes of ortho-substituted Benzalidene Thiosemicarbazones - Prasad Singh, Parashuram; Krishna Thakur, Ajit; Pandit, R.S.; Thakur, B.G. (Asian Journal of Chemistry, 2016)
Oxotitanium (IV) complexes of ortho-substituted benzaldehyde thiosemicarbazones of composition [TiOL2(H2O)] (HL = thiosemicarbazones of 4,4-dimethyl-N-thiosemicarbazide, 4,4-diethyl-N-thiosemicarbazide and 4,4-dibutyl-N-thiosemicarbazide of ortho-Cl, -Br, -NO2 and -OCH3 benzaldehyde) have been prepared and characterized by UV, IR, electrical conductance and magnetic susceptibility measurements.